A steady-state model of a non-walrasian economy with three imperfect markets - Etienne Wasmer (Institute for the Study of Labor (IZA), 2011)
Unemployment may depend on equilibrium in other markets than the labor markets. This paper adresses this old idea by introducing search frictions on several markets: in a model of credit and labor market imperfections as in Wasmer and Weil (2004), I further introduce search on the goods market. The model can be solved by blocks: on two of the three markets, the relevant market tightness is a constant of parameters. In particular, goods market tightness, expressed as the ratio of unmatched consumers to unmatched firms, is equal to 1 which corresponds to a stochastic Say's law: demand and supply are stochastically in equilibrium. Financial market tightness is also a function of three parameters related to financial frictions. Job creation and employment depend on the equilibrium in the other markets. Reciprocally, higher job destruction implies more volatility of income of individual consumers and higher destruction of consumption matches. This lowers profits and further reduces job creation. Finally, there are complementarities between frictions in each market: in particular, the marginal effect of financial frictions on equilibrium unemployment is amplified by goods market frictions and vice versa.
urn:nbn:de:101:1-201106202111
Keywords: J6; E12; E13; 330; search; matching; unemployment; goods market imperfections